Warthin Tumor Incidentally Detected on PET/CT Showing Both 68Ga-DOTANOC and 18F-FDG Uptake. (February 2021) - Vaz, Sofia C.; Marques, Andreia; Lourenço, João; Galzerano, Antonio
Abstract : Abstract: A patient with moderately differentiated pancreatic neuroendocrine tumor with synchronous multifocal liver metastases was referred for further staging with PET/CT. The examinations were performed on 2 consecutive days and showed mild 68 Ga-DOTANOC and intense 18 F-FDG uptake in an incidental right parotid nodule. Differential diagnoses include primary or metastatic neuroendocrine tumor, malignant or benign primary parotid tumor, and intraparotid lymph node. Histology revealed characteristics of a Warthin tumor. While focal FDG uptake in Warthin tumor is frequently described, the somatostatin expression was rarely reported. This clinical case describes 68 Ga-DOTANOC and 18 F-FDG uptake in a parotid Warthin tumor histologically confirmed.